Protein arginylation of cytoskeletal proteins in the muscle: modifications modifying function - Rassier, Dilson E. (Am J Physiol Cell Physiol, 2019)
The cytoskeleton drives many essential processes in normal physiology, and its impairments underlie many diseases, including skeletal myopathies, cancer, and heart failure, that broadly affect developed countries worldwide. Cytoskeleton regulation is a field of investigation of rapidly emerging global importance and a new venue for the development of potential therapies. This review overviews our present understanding of the posttranslational regulation of the muscle cytoskeleton through arginylation, a tRNA-dependent addition of arginine to proteins mediated by arginyltransferase 1. We focus largely on arginylation-dependent regulation of striated muscles, shown to play critical roles in facilitating muscle integrity, contractility, regulation, and strength.